Polymerase chain reaction detection of Pasteurella multocida type B: 2 in mice infected with contaminated river water - Abdullah, Faez Firdaus Jesse; Khaleel, Mohammed Muqdad; Adamu, Lawan; Osman, Abdinasir Yusuf; Haron, Abd Wahid; Saad, Mohd Zamri; Omar, Abdul Rahman (Science Publications, 2013)
Hemorrhagic septicemia is an acute, deadly disease of cattle and buffaloes associated with colossal economic loss in the livestock industry in the Asian regions particularly Malaysia. Therefore, this study was conducted to investigate on the Polymerase chain reaction detection of Pasteurella multocida type B: 2 in mice inoculated through different routes with river water contaminated with infected mice carcasses. Sixty five mice were used for the study; five mice were placed in each tank containing river water for 24, 48 and 72 h. The groups comprise of five mice each made up of the control, intraperitoneal, oral and the aerosol routes. A dose of 1 mL 109 CFU of Pasteurella multocida type B: 2 obtained from the infected river water were inoculated into each group intraperitoneally and the aerosol route while, 0.4 mL of 109 CFU of Pasteurella multocida type B: 2 was inoculated orally into the group. The control group was inoculated with 1 mL buffer saline pH 7. The PCR results in the present study revealed the presence of P. multocida type B: 2 from the following organs brain, kidney, heart, spleen, lung and liver in the mice inoculated through intraperitoneal, oral and aerosol route. In the river water kept for 24 h P. multocida type B: 2 were detected in the organs through the intraperitoneal, oral and the aerosol routes. The river water kept for 48 and 72 h were positive for the isolation of P. multocida inoculated via the intraperitoneal and oral route, except the aerosol route where no significant P. multocida was detected in the organs using PCR. In conclusion, this model could be used to enhance the understanding of the progression of the disease and control of the natural disease through the various routes of the disease transmission. This study also postulated that the outbreak of HS among buffaloes and cattle could be due to the consumption of river water contaminated with infected HS carcasses.